2011
DOI: 10.1002/j.1556-6678.2011.tb00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Play Therapy in Elementary Schools: A Best Practice for Improving Academic Achievement

Abstract: This pilot study of 1st graders who are academically at risk examined the effectiveness of child‐centered play therapy (CCPT). The experimental group received biweekly, 30‐minute play therapy sessions for 8 weeks. Findings indicated that these 1st graders participating in CCPT (n = 21) demonstrated a statistically significant increase on the Early Achievement Composite of the Young Children's Achievement Test (Hresko, Peak, Herron, & Bridges, 2000) when compared with children in the control group (n = 20). Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 26 publications
1
101
0
1
Order By: Relevance
“…Inviting school-based counselors trained in effective and responsive interventions for children can help alleviate the responsibilities of school counselors while still meeting the needs of children (Bratton, 2010;Meany-Walen, Bratton, & Kottman, 2014;Meany-Walen, Kottman, Bullis, & Dillman Taylor, in press;Ray, 2007). Play therapy has been found to be an effective intervention for children and several studies have demonstrated the effectiveness of school-based play therapy interventions (e.g., Blanco & Ray, 2011;Garza & Bratton, 2005;Meany-Walen et al, 2014, in press;Ray, 2007;Schottelkorb & Ray, 2009). Sweeney, Baggerly, and Ray stated, "[G]roup play therapy is not only a powerful therapeutic intervention, but it often provides a more compelling and expedient milieu than individual therapy" (2014, p. 1).…”
Section: Off-task Behaviorsmentioning
confidence: 97%
“…Inviting school-based counselors trained in effective and responsive interventions for children can help alleviate the responsibilities of school counselors while still meeting the needs of children (Bratton, 2010;Meany-Walen, Bratton, & Kottman, 2014;Meany-Walen, Kottman, Bullis, & Dillman Taylor, in press;Ray, 2007). Play therapy has been found to be an effective intervention for children and several studies have demonstrated the effectiveness of school-based play therapy interventions (e.g., Blanco & Ray, 2011;Garza & Bratton, 2005;Meany-Walen et al, 2014, in press;Ray, 2007;Schottelkorb & Ray, 2009). Sweeney, Baggerly, and Ray stated, "[G]roup play therapy is not only a powerful therapeutic intervention, but it often provides a more compelling and expedient milieu than individual therapy" (2014, p. 1).…”
Section: Off-task Behaviorsmentioning
confidence: 97%
“…More related to the debate of play and learning dichotomy, sufficient studies have proven that structured play lead to better academic outcomes, and these advantages have lasting influence on children's later formal schooling life [33]. Guided play can increase children's learning motivation, improve children's language and literacy level [34], and develop children's logical and mathematical thinking, as well as their spatial skills [19].…”
Section: Compatibility Of Play and Learningmentioning
confidence: 99%
“…Another recent treatment study, conducted by some of the same authors and using almost identical study design as Bratton et al (2013), provided evidence for Adlerian play therapy as another level 2 treatment for disruptive behavior (Meany-Walen, Bratton, & Kottman, 2014). While the remainder of play therapy interventions published since the year 2000 remain at level 4, there has been a growing number of 21st-century experimental and quasi-experimental research studies indicating positive treatment effects for several presenting problems, including internalizing problems (Packman & Bratton, 2003), ADHD (Ray, Schottelkorb, & Tsai, 2007), trauma (Schottelkorb, Doumas, & Garcia, 2012;Tyndall-Lind, Landreth, & Giordano, 2001;Shen, 2002), academic problems (Blanco & Ray, 2011), delayed language skills (Danger & Landreth, 2005), teacher-child relationship problems (Ray, 2007;Ray, Henson, Schottelkorb, Brown, & Muro, 2008), and adaptation to medical problems (Bloch & Toker, 2008;Jones & Landreth, 2002;Li & Lopez, 2007;Tsai et al, 2013). The empirical evidence for medical play therapy is particularly notable for its methodological strengths and promising results.…”
Section: Play Therapy Research In the 21st Century And Individual Stumentioning
confidence: 99%
“…This review of 21st century peer-reviewed and published nonfilial play therapy studies identified 18 experimental studies (Blanco & Ray, 2011;Bratton et al, 2013;Carpentier, Silovsky, & Chaffin, 2006;Danger & Landreth, 2005;Fall et al, 2002;Garza & Bratton, 2005;Jones & Landreth, 2002;Li et al, 2008;Meany-Walen et al, 2014;Packman & Bratton, 2003;Paone, Packman, Maddux, & Rothman, 2008;Ray, 2007;Ray et al, 2007Ray et al, , 2008Schottelkorb et al, 2012;Shen, 2002;Tsai et al, 2013;Wang Flahive, & Ray, 2007). While randomization is often difficult when designing an intervention-based research design, play therapy researchers have clearly responded to the need for RCTs.…”
Section: Group Designmentioning
confidence: 99%
See 1 more Smart Citation